2015
DOI: 10.1039/c5ee02051d
|View full text |Cite
|
Sign up to set email alerts
|

Sodium intercalation chemistry in graphite

Abstract: The insertion of guest species in graphite is the key feature utilized in applications ranging from energy storage and liquid purification to the synthesis of graphene. Recently, it was discovered that solvated-Naion intercalation can occur in graphite even though the insertion of Na ions alone is thermodynamically impossible; this phenomenon enables graphite to function as a promising anode for Na-ion batteries. In an effort to understand this unusual behavior, we investigate the solvated-Na-ion intercalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
409
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(434 citation statements)
references
References 36 publications
19
409
3
3
Order By: Relevance
“…Recently, Cohn et al 51 showed stable capacity of ca. 150 mA h g −1 , suggesting a stoichiometry of Na(Diglyme) x C 15 , that is in agreement with previous reports on chemically derived stage 1 Na + ternary graphite intercalation compounds (GICs). Figure 10 shows a 1D Patterson diagram along the c-axis calculated from the XRD (00l) peak intensities.…”
Section: Gsm-b Gsm-br G Dsupporting
confidence: 80%
See 2 more Smart Citations
“…Recently, Cohn et al 51 showed stable capacity of ca. 150 mA h g −1 , suggesting a stoichiometry of Na(Diglyme) x C 15 , that is in agreement with previous reports on chemically derived stage 1 Na + ternary graphite intercalation compounds (GICs). Figure 10 shows a 1D Patterson diagram along the c-axis calculated from the XRD (00l) peak intensities.…”
Section: Gsm-b Gsm-br G Dsupporting
confidence: 80%
“…Upon a first discharge, a new set of (00l) ) unless CC License in place (see abstract reflections appeared for TEG, which are indexed as belonging to the stage-1 of the Na x (DGM) 2 C 20 compound. 15,16 Then, upon charging the initial position of the (002) reflection is retrieved, evidencing the reversibility of the insertion process. Its enhanced broadening involves a structural modification of the interlayer spacing to allow sodium diffusion.…”
Section: Gsm-b Gsm-br G Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hard carbon, which is associated with a high production cost and low material's density, must be used as an anode in NIBs, as graphite, which is the standard anode for LIBs, cannot store Na ions. [15][16][17] Recently, K-ion batteries (KIBs) have emerged as another possible energy storage system. [18][19][20] It is notable that the abundance of K resources in the Earth's crust and oceans is similar to that of Na (Figure 1a).…”
mentioning
confidence: 99%
“…Tr otz der Grçße des solvatisierten Ions ist die Elektrodenreaktion hochreversibel und weist eine ausgezeichnete Kinetik auf.D arüber hinaus kann das Redoxpotential gezielt eingestellt werden, indem die Art des Etherlçsungsmittels variiert wird. [89] Da solvatisierte Ionen sehr groß sind, ist mçglicherweise auch eine Exfoliation des Graphitgitters zu erwarten. Allerdings wurde kürzlich postuliert, dass Va n-der-Waals-Wechselwirkungen zwischen den Graphenschichten und den kointerkalierten Lçsungsmittelmole-külen die Schichtstruktur stabilisieren.…”
Section: Graphit Und Andere Kohlenstoffeunclassified